170k views
5 votes
Simplify (1-cos theta)(1+cos theta) over (1-sin theta) (1+ sin theta)

User Lenis
by
6.0k points

1 Answer

2 votes

\bf sin^2(\theta)+cos^2(\theta)=1\to \begin{cases} cos^2(\theta)=1-sin^2(\theta)\\ sin^2(\theta)=1-cos^2(\theta) \end{cases} \\\\ -------------------------------\\\\ \stackrel{\textit{difference of squares}}{\cfrac{[1-cos(\theta )][1+cos(\theta )]}{[1-sin(\theta )][1+sin(\theta )]}}\implies \cfrac{1^2-cos^2(\theta )}{1^2-sin^2(\theta )}\implies \cfrac{1-cos^2(\theta )}{1-sin^2(\theta )} \\\\\\ \cfrac{sin^2(\theta )}{cos^2(\theta )}\implies tan^2(\theta )
User Codus
by
5.3k points